Peran teknologi dalam meningkatkan Ketahanan Nasional melalui Sumber Daya Manusia yang lebih baik - Putri, Eka Amalia; Permatasari, Berliana Atika; Imama, Garnis Isma Ahsanal; Bachty, Salsabila Rayhananda (Maliki Interdisciplinary Journal, 2024)
National resilience is a state produced by a process that involves various aspects such as ideology, economy, politics, socio-culture, as well as defense and security. National resilience must be built on the cultural roots of the Indonesian nation itself and must be resolved through a cultural approach. The implementation of national resilience is carried out through a security and welfare approach, with the aim of realizing the nation’s ability to grow and develop its national values into fair and equitable prosperity. This research method includes qualitative research, which is a type of library research. It includes an approach based on the geographical situation of each region and the building human resources. The result that will be reaped is that the Indonesian nation can face the threats, disturbances, obstacles, and challenges that come. Therefore, further efforts need to be made to build national resilience so that Indonesian geese can remain upright and face the challenges that come better together.